2012
DOI: 10.1111/j.1365-277x.2012.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of digestive tolerance of a soluble corn fibre

Abstract: The results of the present study demonstrate that 40 g of SGF fibre, when consumed as a single dose, and 65 g of SGF fibre, when consumed in multiple-doses, across the day are well-tolerated by healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…overall score <4). These results are in agreement with previous studies [ 32 , 33 , 41 , 42 , 43 , 44 ] on the digestive tolerance of prebiotics, including those determined in a single amount up to 65 g fibre/d [ 45 ]. The authors also concluded that SCF was well tolerated at daily amounts as high as 65g [ 45 ], whereas some candidate prebiotic fibres have been shown to induce a mild laxation effect, increasing stool frequency and weight when consumed at high doses (>20 g/day)…”
Section: Discussionsupporting
confidence: 93%
“…overall score <4). These results are in agreement with previous studies [ 32 , 33 , 41 , 42 , 43 , 44 ] on the digestive tolerance of prebiotics, including those determined in a single amount up to 65 g fibre/d [ 45 ]. The authors also concluded that SCF was well tolerated at daily amounts as high as 65g [ 45 ], whereas some candidate prebiotic fibres have been shown to induce a mild laxation effect, increasing stool frequency and weight when consumed at high doses (>20 g/day)…”
Section: Discussionsupporting
confidence: 93%
“…However, the cutoff of tolerability will likely differ per prebiotic and individual. Also the method of application may be of importance as it has been reported that soluble corn fiber is well tolerated up to 65 g/day, but only when consumed in multiple doses (158). Related to this point is the fact that none of the studies reporting on gut microbiota changes by supplemental carbohydrates assessed the regular dietary micro-/macronutrient and fiber composition of the participants.…”
Section: The Choice Of Supplemental Fermentable Carbohydratesmentioning
confidence: 99%
“…A small but statistically significant increase in flatulence and stomach noises compared to a placebo condition (ranked on a scale of 1¼ minimal, 10¼ excessive) was reported. More recently, a single dose up to 40 g/serving, as well as dosages up to 65 g/d spread out over a day, has been shown to be well tolerated in healthy adults (Housez et al 2012). In this study, incidental GI symptoms including bloating, abdominal cramping, stomach noises and flatulence were reported at every dose, but symptoms were usually rated as mild and were not significantly different from control.…”
Section: Discussionmentioning
confidence: 65%